Model Pengembangan Pendidikan Islam Bagi Kelompok Milenial (Studi Kasus di Kafe Basa Basi Sorowajan Banguntapan Bantul Yogyakarta) - Ahmad Sangidu; fajrus shodiq (Tafhim Al-'Ilmi, 2021)
The purpose of this study was to find out about the Cafe Basabasi Sorowajan Banguntapan Bantul. There are many religious activities, including: Selawat Burdah, public lectures, and free takjil. In fact, the majority of cafes are only used as a place to hangout and have coffee. In addition, the majority of visitors are millennial groups. Based on some of the things he mentioned above, this study aims to answer questions about the model of developing Islamic education for millennial groups, the reasons for teaching Islamic education, and its implications for the religious behavior of millennial groups. This research is a field research (field research). Data collection is done by means of observation, interviews, and documentation. Meanwhile, the data analysis used Miles and Huberman's model. The validity of the data in this study used a credibility test with triangulation. The results of this study can be concluded that the integrated Islamic education development model for millennial groups at the Basabasi Sorowajan Bantul Café is found in activities: semaan Al-Qur'an, Selawat Burdah, free takjil, and public lectures. Keywords: Integrative. Millennial.